Disseminated histoplasmosis: case report and review of the literature. Issue 5 (3rd September 2018) - Evrard, Séverine; Caprasse, Philippe; Gavage, Pierre; Vasbien, Myriam; Radermacher, Jean; Hayette, Marie-Pierre; Sacheli, Rosalie; Van Esbroeck, Marjan; Cnops, Lieselotte; Firre, Eric; Médart, Laurent; Moerman, Filip; et al.
Abstract: Case report We report the case of a young Cameroonian woman who presented with cough, hyperthermia, weight loss, pancytopenia, and hepatosplenomegaly. A positive HIV serology was discovered and a chest radiography revealed a 'miliary pattern'. Bone marrow aspiration pointed out yeast inclusions within macrophages. Given the morphological aspect, the clinical presentation and immunosuppression, histoplasmosis was retained as a working hypothesis. Antiretroviral and amphotericin B treatments were promptly initiated. Review Given the immigration wave that Europe is currently experiencing, we think it is important to share experience and knowledge, especially in non-endemic areas such as Europe, where clinicians are not used to face this disease. Histoplasmosis is due to Histoplasma capsulatum var. capsulatum, a dimorphic fungus. Infection occurs by inhaling spores contained in soils contaminated by bat or bird droppings. The clinical presentation depends on the immune status of the host and the importance of inoculum, varying from asymptomatic to disseminated forms. AIDS patients are particularly susceptible to develop a severe disease. Antigen detection, molecular biology techniques, and microscopic examination are used to make a rapid diagnosis. However, antigen detection is not available in Europe and diagnosis needs a strong clinical suspicion in non-endemic areas. Because of suggestive imagery, clinicians might focus on tuberculosis. Our case illustrates the need for clinicians to take histoplasmosis in the differential diagnosis, depending on the context and the patient's past history.